Significant Association Between Snapping Scapula Syndrome and Anterior Angulation of the Superomedial Scapular Angle. Issue 7 (29th July 2014) - Millett, Peter J.; Smith, Sean; Ho, Charles; Spiegl, Ulrich
Objectives: Significant Association Between Snapping Scapula Syndrome and Anterior Angulation of the Superomedial Scapular Angle. Methods: In this Institutional Review Board approved study, bony morphologies of the scapula were evaluated on the MRIs of 28 patients (28 scapulae) with SSS and 20 patients (22 scapulae) with non-SSS pathologies. Patients with SSS were identified from a prospective surgical registry that had undergone a preoperative shoulder MRI along with scapular bursectomy and/or superomedial angle resection. The non-SSS patients underwent shoulder MRIs for other reasons that subsequently allowed for evaluation of the scapula. The medial scapula corpus angle (MSCA), was measured on axial STIR or PD FSE sequences cranial to the spine of the scapula (Figure 1). Scapula length angled towards rib cage was documented. Scapulae were categorized as straight, s-shaped or concave. Two blinded observers, one radiologist and one orthopedic surgeon, reviewed all MRIs. MSCAs were measured using Stryker OfficePACS Power 4.1 Express Edition (Kalamazoo, MI). Positive MSCAs were defined as anterior scapular angulation towards the thorax in the axial plane whereas negative MSCAs were defined as posterior scapular angulation away from the thorax in the axial plane. Results: Axial scapula corpus configurations were identified: 31 scapulae were of the straight type, 14 were s-shaped and 5 were concave. All five concave scapulae had surgically confirmed SSS. The measurement of MSCA had excellent inter-observer agreement of 0.81 [95% CI, 0.68 to 0.89] and a fair to good intra-observer agreement of 0.68 [95% CI, 0.50 to 0.80]. There were significant differences in the mean MSCAs between those with SSS (14.4° ± 19.3°) and those with other pathologies (-3.3° ± 15.3°; p = 0.001). After excluding all concave scapulae (n = 5), the differences in the mean MSCAs between the SSS and non-SSS groups were significant (MSCA for SSS: 15.3° ± 17.5° MSCA for non-SSS: -3.3° ± 15.3°; p < 0.0001). Twenty of 28 (71.4%) scapulae with a positive MSCA had SSS, whereas only 3 of 17 (25%) scapulae with a negative MSCA had SSS (see Figure 1). The mean length of the medial scapula border angled to towards the rib cage was 14.4 mm (± 4.6 mm). Conclusion: Anterior angulation of the superomedial angle in the axial plane had an association with SSS. Those patients with a concave-shaped scapula and a positive MSCA may be at risk for SSS. This information may have clinical relevance in the treatment of SSS patients since there are no guidelines on the amount of scapular resection may or may not be needed. The MSCA may prove helpful in determining the location and amount of scapula resection needed to reduce SSS symptoms in patients.